1983
DOI: 10.1128/aem.45.2.536-545.1983
|View full text |Cite
|
Sign up to set email alerts
|

Legionella oakridgensis: unusual new species isolated from cooling tower water

Abstract: We describe a new species of Legionella represented by 10 strains isolated from industrial cooling towers. Legionella oakridgensis differed genetically from the other seven species of Legionella in DNA hybridization studies and differed serologically in direct fluorescent-antibody tests. The new species, unlike all other species except L. jordanis, did not require added L-cysteine for growth in serial transfer on charcoal-yeast extract agar. L. oakridgensis, as well as three other species tested, required L-cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Like other legionellae, L. sainthelensi contains relatively large amounts (50 to 62%) of the total acids as branched-chain acids (4,6,(16)(17)(18). Quantitatively, the fatty acid composition of L. sainthelensi is most similar to those of L. bozemanii (4,14,18), L. Iongbeachae (16), L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other legionellae, L. sainthelensi contains relatively large amounts (50 to 62%) of the total acids as branched-chain acids (4,6,(16)(17)(18). Quantitatively, the fatty acid composition of L. sainthelensi is most similar to those of L. bozemanii (4,14,18), L. Iongbeachae (16), L.…”
Section: Resultsmentioning
confidence: 99%
“…The fatty acids of these six isolates are qualitatively similar to those of other Legionella species with the characteristic features of the presence of isobranched-chain 14-and 16-carbon acids (i-14:0, i-16:0) and anteisobranched-chain 15-and 17-carbon acids (a-15:0, a-17:0) together with relatively large amounts of a monounsaturated straight-chain 16-carbon acid (16:1) and the absence of individual hydroxy acids at concentrations greater than 1% (6,(16)(17)(18). Like other legionellae, L. sainthelensi contains relatively large amounts (50 to 62%) of the total acids as branched-chain acids (4,6,(16)(17)(18). Quantitatively, the fatty acid composition of L. sainthelensi is most similar to those of L. bozemanii (4,14,18), L. Iongbeachae (16), L.…”
Section: Resultsmentioning
confidence: 99%
“…This organism is apparently found worldwide, as evidenced by documented outbreaks in Europe, Israel, Scandinavia, and Australia (6). Since 1976, eight additional serogroups of L. pneumophila and seven additional species have been recognized (2,26). Legionella bacteria have been responsible for numerous focal outbreaks of pneumonia as well as isolated cases, with many of the latter appearing in immunocompromised hosts (5).…”
mentioning
confidence: 99%
“…Various experimental studies and the analysis of various genome sequences revealed that L. pneumophila is auxotrophic for Arg, Cys, Ile, Leu, Met, Thr and Val, and the amino acids Arg, Cys, Ile, Leu, Met, (Phe), Ser, Thr, (Tyr) and Val are essential for growth . Cysteine is absolutely required for the growth of legionellae, and media must be supplemented with cysteine to support growth of L. pneumophila , but this is not true for L. oakridgensis , a less virulent Legionella species . Generally, genes for serine‐O‐acetyltransferase and cysteine synthase are not present in the genome sequences of legionellae, with the exception of L. oakridgensis .…”
Section: Metabolic Features Of L Pneumophila In Vitromentioning
confidence: 99%